(untitled) (Zaporizhzhia Historical Review, 2021)
The article examines the vision of Islam in USA today. It is discovered the factors that produced Muslim bias and negative stereotypes, such as European heritage, US foreign policy, last years acts of terrorism and so on. Special consideration is given to attitude toward Islam and Muslims in the academical researches.